The Holy Spirit and the Church according to the New Testament Sixth International East-West Symposium of New Testament Scholars, Belgrade, August 25 to 31, 2013 - Niebuhr, Karl-Wilhelm; Karakolis, Christos; Dragutinović, Predrag; Wallace, James Buchanan; Wallace, James Buchanan (Mohr Siebeck, 2016)
Der Heilige Geist und die Kirche im Neuen Testament. Sechstes Internationales Ost-West Symposium der Neutestamentler, Belgrad, 25.-31. August 2013.
PublicationDate: 20200805
Keywords: Paul -- Gospel of John -- Hermeneutics -- Biblical Exegesis -- Luke-Acts -- Jesus Research -- Ecumenical Theology -- Orthodox theology -- Kartellrechtliche Zwangslizenzen -- Neues Testament -- Kirchengeschichte -- Array